THE ROLE OF THE FAMILY PSYCHOLOGY COURSE IN FORMING PREVENTIVE AWARENESS OF DIVORCE AMONG ISLAMIC FAMILY LAW STUDENTS OF STDI IMAM SYAFI'I JEMBER (QUALITATIVE STUDY) - Ilham Fadhilah Putra; Misbahuzzulam Misbahuzzulam (Journal Analytica Islamica, 2026)
The increasing divorce rate in Indonesia indicates that family issues are not only related to legal aspects, but are also influenced by psychological factors, such as communication, emotional management, and conflict resolution skills. In this context, the Family Psychology course plays a role in developing preventive awareness of divorce, especially among Islamic Family Law students who will face various family issues in society. This study aims to analyze the role of the Family Psychology course in developing preventive awareness of divorce among students of the Islamic Family Law Study Program at STDI Imam Syafi'i Jember. This study uses a qualitative method with a case study approach. Data were obtained through in-depth interviews with six students who have or are currently taking the Family Psychology course, supported by documentation and previous research reviews. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Family Psychology course plays a role in developing students' understanding of family dynamics and the importance of communication, emotional regulation, conflict management, empathy, and understanding of roles within the family as an effort to maintain household harmony. Most informants experienced changes in understanding after attending the course, although the level of influence felt varied according to each individual's initial knowledge and learning experience. This study confirms that the integration of family psychology and Islamic family law perspectives can contribute to building preventive awareness of divorce and become the basis for developing more participatory and contextual learning in Islamic higher education environments.